THE EFFECTIVENESS OF PERSONAL DILEMMA TECHNIQUE ON TEACHING SPEAKING SKILL FOR EFL LEARNERS - asrobi, maman (Universitas Hamzanwadi, 2015)
This study aims at investigating the effectiveness of personal dilemma technique on teaching speaking skill for EFL learners. Designed as pre-experimental research with pretest-posttest design, it examined a sample of first semester of English department of STKIP Hamzanwadi Selong in the school year 2014-2015. Random sampling technique was used in determining the sample of the study. Speaking test and analytical scoring rubric were the instruments used to collect the data. Then the data were analyzed by using descriptive statistic and paired sample t-test to test the hypothesis. The result of descriptive statistic analysis revealed that personal dilemma technique is effective for teaching speaking for EFL learners since the mean score of posttest 71.85 was higher than mean score of pretest 61.28. While for hypothesis testing by using paired sample t-test at significance (2-tailed) value level was .000, it was lower than .05. So, it means that the hypothesis of this study was accepted. In other word, personal dilemma technique was significantly effective in improving students’ speaking ability of the first semester students of English department of STKIP Hamzanwadi Selong in the school year 2014-2015.